Neutrophil percentage to albumin ratio is associated with stroke-associated pneumonia and poor outcome in patients with spontaneous intracerebral hemorrhage - Lv, Xin-Ni; Shen, Yi-Qing; Li, Zuo-Qiao; Deng, Lan; Wang, Zi-Jie; Cheng, Jing; Hu, Xiao; Pu, Ming-Jun; Yang, Wen-Song; Xie, Peng; Li, Qi (Frontiers in Immunology, 2023)
Background: The purpose of this study was to investigate the diagnostic performance of the neutrophil percentage-to-albumin ratio (NPAR) for predicting stroke-associated pneumonia (SAP) and functional outcome in patients with intracerebral hemorrhage (ICH). Methods: We analyzed our prospective database of consecutive ICH patients who were admitted to the First Affiliated Hospital of Chongqing Medical University from January 2016 to September 2021. We included subjects with a baseline computed tomography available and complete NPAR count performed within 6h from onset. The patients’ demographic and radiological characteristics were analyzed. Good outcome was defined as modifed Rankin Scale score of 0-3 at 90 days. Poor outcome was defined as modifed Rankin Scale score of 4-6 at 90 days. Multivariable logistic regression models were used to investigate the association between NPAR, SAP and functional outcome. Receiver operating characteristic (ROC) curve analysis was conducted to identify the optimal cutoff of NPAR to discriminate between good and poor outcome in ICH patients. Results: A total of 918 patients with ICH confirmed by non-contrast computed tomography were included. Of those, 316 (34.4%) had SAP and 258 (28.1%) had poor outcome. Multivariate regression analysis showed that higher NPAR on admission was an independent predictor of SAP (adjusted odds ratio: 2.45; 95% confidence interval, 1.56-3.84; P<0.001) and was associated with increased risk of poor outcome (adjusted odd ratio:1.72; 95% confidence interval, 1.03–2.90; P=0.040) in patients with ICH. In ROC analysis, a NPAR of 2 was identified as the optimal cutoff value to discriminate between good and poor functional outcome. Conclusion: Higher NPAR is independently associated with SAP and poor functional outcome in patients with ICH. Our findings suggest that early prediction of SAP is feasible by using a simple biomarker NPAR.